2007
DOI: 10.3892/ijmm.20.4.621
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative expression of the homeobox and integrin genes in human gastric carcinoma

Abstract: Abstract. The homeobox (HOX) genes are a large family of regulator genes involved in the control of developmental processes and cell differentiation. The HOX genes encode transcription factors, and an increasing number of studies have shown that these genes may be implicated in the growth and the progression of many types of tumours. The present study investigated the expression of the HOX and integrin genes and their relationships in gastric carcinoma. We analyzed the RNA expression of 13 HOX genes from HOXA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…ClassⅠ human homeobox-containing genes (HOX genes) have been reported to act as a network of transcriptional regulators involved in the process of cell to cell communication during normal morphogenesis, the alteration of which may contribute to the evolution of cancer [8] . Moreover, a recent study concluded that HOX genes may play a critical role in the genesis and progression of gastric cancer [9] .…”
Section: Discussionmentioning
confidence: 99%
“…ClassⅠ human homeobox-containing genes (HOX genes) have been reported to act as a network of transcriptional regulators involved in the process of cell to cell communication during normal morphogenesis, the alteration of which may contribute to the evolution of cancer [8] . Moreover, a recent study concluded that HOX genes may play a critical role in the genesis and progression of gastric cancer [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous genes are differentially expressed during colon carcinogenesis (Bhatlekar, Fields, & Boman, ; Bhatlekar, Viswanathan, Fields, & Boman, ; Boman, Fields, Cavanaugh, Guetter, & Runquist, ; Eberhart et al, ; Gardina et al, ; Lee, Bang, Song, & Lee, ) indicating that regulatory mechanisms involved in tumor development are complex, but deciphering which regulatory mechanisms contribute to colorectal cancer (CRC) needs further clarification. We and others have reported that expression of HOX genes, which are key regulators of stem cells (SCs) during embryogenesis, becomes dysregulated in numerous cancers including colon cancer (Bhatlekar, Fields, et al, ; Freschi et al, ). Our previous studies showed that HOXA4, HOXA9 , and HOXD10 are aberrantly expressed in CRC (Bhatlekar, Addya, et al, ; Bhatlekar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ectopic expression of CDX1 and CDX2 induced the development of intestinal metaplasia of the gastric mucosa in a transgenic mouse model, and their expression levels were significantly increased in gastric adenoma or adenocarcinoma compared with surrounding non‐tumorous tissues in humans . However, recent studies have investigated the global expression of HOX genes and differences in expression levels between normal stomach and gastric adenocarcinoma tissues, and additional studies are required to evaluate the roles of specific HOX genes in gastric carcinogenesis. A recent study examined the expression of all 39 HOX genes in human stomach tissues and compared cancer tissues with non‐tumorous tissues using microarray methods .…”
Section: Introductionmentioning
confidence: 99%